STRESS INDUCED FACTOR 2 Regulates Arabidopsis Stomatal Immunity through Phosphorylation of the Anion Channel SLAC1. Issue 7 (23rd April 2020) - Chan, Ching; Panzeri, Dario; Okuma, Eiji; Tõldsepp, Kadri; Wang, Ya-Yun; Louh, Guan-Yu; Chin, Tzu-Chuan; Yeh, Yu-Hung; Yeh, Hung-Ling; Yekondi, Shweta; Huang, You-Huei; Huang, Tai-Yuan; et al.
Abstract : SIF2 is critical for Arabidopsis ( Arabidopsis thaliana ) resistance to bacteria by regulating stomatal immunity, belongs to the FLS2/BAK1 immunity receptor complex, and phosphorylates the anion channel SLAC1. Abstract: Upon recognition of microbes, pattern recognition receptors (PRRs) activate pattern-triggered immunity. FLAGELLIN SENSING2 (FLS2) and BRASSINOSTEROID INSENSITIVE1-ASSOCIATED KINASE1 (BAK1) form a typical PRR complex that senses bacteria. Here, we report that the kinase activity of the malectin-like receptor-like kinase STRESS INDUCED FACTOR 2 (SIF2) is critical for Arabidopsis ( Arabidopsis thaliana ) resistance to bacteria by regulating stomatal immunity. SIF2 physically associates with the FLS2-BAK1 PRR complex and interacts with and phosphorylates the guard cell SLOW ANION CHANNEL1 (SLAC1), which is necessary for abscisic acid (ABA)-mediated stomatal closure. SIF2 is also required for the activation of ABA-induced S-type anion currents in Arabidopsis protoplasts, and SIF2 is sufficient to activate SLAC1 anion channels in Xenopus oocytes. SIF2-mediated activation of SLAC1 depends on specific phosphorylation of Ser 65. This work reveals that SIF2 functions between the FLS2-BAK1 initial immunity receptor complex and the final actuator SLAC1 in stomatal immunity.